Silicate fertilization on productivity and physiological responses of plants (Research, Society and Development, 2022)
Silicon is the second most abundant element in the earth's crust, corresponding to 27.7% of its composition. However, in tropical soils, most of this Si is unavailable to plants. Even though it is not an essential element, Si supplementation generates benefits to crops. The objective of this work was to combine data from multiple studies on silicon adduction in order to clarify the effects on productivity, induction of resistance to pests, diseases and conditions of salinity and water deficit. The review addressed the following topics: 1) Silicon in the soil 2) Forms of silicon application 3) Effects of silicon fertilization in inducing resistance to salinity 3) The importance of silicon fertilization in plants 4) Agronomic response regarding the effects of silicon fertilization on productivity, resistance to insects, resistance to diseases and tolerance to salinity and water deficit. The use of Si provides effects on the physiology, biochemistry and structure of plants, which gives greater mechanical strength, resistance to biotic and abiotic effects. The effects related to productivity vary according to the crop or cultivar used. In the studies carried out, some beneficial effect related to the use of Si was observed. The benefits are mechanical and biochemical resistance, reduction of stress caused by salinity and water deficit. With the growing need for food, silicate fertilization represents an additional tool for agriculture.